PENERAPAN BIMBINGAN BELAJAR PADA MASA PANDEMI COVID-19 DI DESA LIKONGGETE - Rosmawati Rosmawati; Sahrunayanti Sahrunayanti (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
The existence of the Covid-19 pandemic has made the Indonesian government establish a policy to study from home through the online system. This resulted in learning difficulties for students. This difficulty is caused by the unpreparedness of students and schools in dealing with policy changes. Seeing this, this is the village's main priority in making literacy activities to increase the understanding of school students in Likonggete Village. Based on this, the purpose of service is to increase student literacy. The method used is the socialization of activities by carrying out study guidance activities. Based on the results of this tutoring activity dedication can help parents who cannot accompany their children in participating in online learning and also to increase the learning motivation of elementary school students who live in the Likonggete Preparation Village.